2012
DOI: 10.1590/s0037-86822012000600020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism for IFNγ +874T/A in patients with acute toxoplasmosis

Abstract: Introduction: A single nucleotide polymorphism (SNP) in the gene encoding gamma interferon influences its production and is associated with severity of infectious diseases. This study aimed to evaluate the association of IFNγ+874T/A SNP with duration of disease, morbidity, and development of retinochoroiditis in acute toxoplasmosis. Methods: A case-control study was conducted among 30 patients and 90 controls. Results: Although statistical associations were not confirmed, A-allele was more common among retinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
1
7
0
3
Order By: Relevance
“…Neves et al (2009) identified the A allele in most of the individuals with toxoplasmosis-related retinochoroiditis (albeit with no statistical significance), also suggesting an association between the A allele in homozygosis and ocular toxoplasmosis. In addition, Neves et al (2012) identified an association between the AA genotype in the SNP +874T>A ( rs2430561 ) and a longer duration of symptoms in the acute stage of disease; however, the association failed to reach statistical significance, which the authors attributed to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neves et al (2009) identified the A allele in most of the individuals with toxoplasmosis-related retinochoroiditis (albeit with no statistical significance), also suggesting an association between the A allele in homozygosis and ocular toxoplasmosis. In addition, Neves et al (2012) identified an association between the AA genotype in the SNP +874T>A ( rs2430561 ) and a longer duration of symptoms in the acute stage of disease; however, the association failed to reach statistical significance, which the authors attributed to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the data reported by Neves et al (2012) indicate that individuals with low-IFN-γ-producer genotypes tend to exhibit a longer duration of symptoms in the acute phase of toxoplasmosis, suggesting an inability to inhibit parasite replication. If this hypothesis is confirmed, i.e., if scar lesions exhibited by high-IFN-γ producers with genotype AA are of congenital origin, then the role we have attributed to IFN-γ in the aggravation of retinochoroidal lesions will have to be reevaluated in the context of ocular toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanto à distribuição dos genótipos e dos alelos no estudo do SNP IFNG +874 T/A, no presente trabalho, houve predomínio do alelo A e menor frequência do genótipo TT nos grupos de pacientes e controles, de acordo com outros estudos na população brasileira (Visentainer et al, 2008;Albuquerque et al, 2009;Matos et al, 2007;Cardoso et al, 2010;Medina et al, 2011;Bozzi et al, 2009;Neves et al, 2012;Pereira et al, 2015).…”
Section: Relação Dos Snpsunclassified
“…Dissertação de Flávia Mendes da Cunha Holanda na toxoplasmose (Neves et al, 2012); e na leishmaniose tegumentar americana (Matos et al, 2007).…”
Section: Relação Dos Snpsunclassified